Penerapan Uji Chi-Square Terhadap Faktor Perilaku Pengelolaan Sampah di Pesisir Leato Selatan - Silfana, Bela; Payu, Muhammad Rezky Friesta (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The waste problem in coastal areas is increasingly worrying due to increasing human activity and low public awareness. One of the main issues is suboptimal waste management practices, such as littering and failure to separate waste types. This study aims to determine the relationship between age, education level, knowledge, attitudes, and availability of facilities with waste management practices in coastal communities. The method used was quantitative with a descriptive analytical design. Primary data were collected from 347 respondents through a validated and reliability-tested questionnaire. The sampling technique used was purposive sampling. Data analysis was performed using the Chi-Square test to examine the relationship between variables. The results showed that attitudes and availability of facilities have a significant relationship with community waste management practices. These factors influence how communities manage waste in coastal areas.